Solving a nomenclatural conundrum: Cernosvitovia crainensis (Mršić, 1989) and Aporrectodea macvensis Šapkarev in Mršić, 1991 (Lumbricidae) - Nicolson, David; Csuzdi, Csaba (Zootaxa, 2018)
This contribution deals with the names and authorship of two lumbricid taxa endemic to the Balkans (see Stojanović et al., this volume). Although their validity has never been questioned, it has been unclear up to now which publication has made these two species-group names available according to the rules of the International Code of Zoological Nomenclature (Articles in "the Code," ICZN 1999). In the following, we review the somewhat intricate history of these names and explain why the correct citation and spelling of these names are "Cernosvitovia crainensis (Mršić, 1989)" and "Aporrectodea macvensis Šapkarev in Mršić, 1991," respectively.